VIPCALL: A design-based method of visual grammar symbols for improving EFL Students’ fiction writing - NUR ANTONI EKO TANUSO; Yan Mujiyanto; Rudi Hartono; Hendi Pratama (Universitas Islam Sultan Agung, 2026)
This mixed-methods DBR study designed and assessed VIPCALL, a web-based multimodal program, which embedded visual grammar symbols into fiction writing instruction for EFL learners. The sample included 50 university students at an intermediate proficiency level who were involved in a 16-week intervention involving needs analysis, symbol development, classroom implementation, and iterative refinement. Quantitative tools included validated grammar pre- and post-tests (Cronbach's α = 0.86) and writing rubrics; qualitative data included classroom video logs, peer debriefings, and student reflections. Change in grammar and writing results were measured with paired-samples t-tests and normalized gain, N-Gain = 0.71; thematic analysis was applied to qualitative data. The findings described here include statistically significant improvements in grammar recognition, writing accuracy, and narrative coherence-mean pre being 119.63 and mean post being 158.93-and self-reported decreases in anxiety, plus heightened engagement and confidence while writing creatively. The study illustrates the effectiveness of visual-symbol scaffolding within a collaborative digital environment as a means to harmonize grammatical accuracy with creative expression and presents practical guidelines on how to integrate symbol-based tools into the pedagogy of EFL writing.